Positive Solutions for Systems of Second-Order Difference Equations. (10th September 2015) - Henderson, Johnny; Luca, Rodica
Abstract : We study the existence and nonexistence of positive solutions of some systems of nonlinear second-order difference equations subject to multipoint boundary conditions which contain some positive constants.